PENERAPAN MODEL PEMBELAJARAN STAD BERBANTUAN QUIZIZ UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA UPT SDN 10 MAKALE - Rati, Yunita; Payung, Zatman; Kabanga', Theresyam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve the reading comprehension skills of fourth-grade students at UPT SDN 10 Makale through the implementation of the Student Teams Achievement Division (STAD) learning model assisted by Quizizz. The study employed a Classroom Action Research (CAR), consisting of two cycles, with each cycle including planning, action, observation, and reflection stages. The research subjects were 21 fourth-grade students, comprising 15 boys and 6 girls. Data were collected through interviews, observations, tests, and documentation. Qualitative data were analyzed using data reduction, data display, and conclusion drawing, while quantitative data were analyzed using mean scores and classical learning mastery percentages. The findings revealed a significant improvement in students' reading comprehension skills after implementing the STAD model assisted by Quizizz. In the first cycle, the average score was 65.71, with a classical learning mastery of 23.8%. After improvements were made in the second cycle, the average score increased to 77.86, and classical learning mastery reached 90.5%, exceeding the predetermined success criterion of 80%. Observation and interview results also indicated increased student participation, motivation, collaboration, and confidence during the learning process. These findings demonstrate that the implementation of the STAD learning model assisted by Quizizz effectively improves students' reading comprehension skills. Keywords: Student Teams Achievement Division (STAD), Quizizz, Reading Comprehension Skills